The Researching History of Theatre (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article deals with the history of sacred history. At the same time, many works of the national spirit created by our theatrical creators are successfully performed abroad. It is appropriate to note that at present many performances on various topics and genres are being created in republican theatres, and a peculiar creative search continues. Theatre must take an equal step over time. Because whatever the period, the theatre lives with the joy and joy of the people.